URBAN BIKE HUB CISAUK - Stefanus Stefanus; Nina Carina (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The Covid-19 pandemic that has occurred has resulted in the emergence of the cycling phenomenon which has returned to life in various countries including Indonesia. The use of bicycles during the pandemic has been shown to be a means of transportation, exercise and recreation. This can have positive consequences both for the city and for the health benefits that are obtained from cycling so that the cycling phenomenon that is rife should be welcomed and supported so that it can become part of the lifestyle to come. Bike Hub, which is located in the Bumi Serpong Damai (BSD) area, has become an embryo for the Jabodetabek area as a building that accommodates park & ride functions oriented towards users of the Cisauk train station, as well as accommodating bicycle hobbyists in the surrounding area. Keywords: commuter; cycling; cyclist; dwellingAbstrakPandemi Covid-19 yang terjadi mengakibatkan munculnya fenomena bersepeda yang kembali marak di berbagai negara tak terkecuali Indonesia. Penggunaan sepeda selama masa pandemi ada yang digunakan sebagai alat transportasi, berolahraga maupun rekreasi. Hal ini dapat berakibat positif baik bagi kota maupun bagi manfaat kesehatan yang didapatkan dari bersepeda sehingga fenomena bersepeda yang sedang marak ini seharusnya disambut dan didukung agar dapat menjadi bagian dari gaya hidup yang akan datang. Bike Hub yang bertempatkan di kawasan Bumi Serpong Damai (BSD) menjadi embrio bagi kawasan Jabodetabek sebagai bangunan yang mewadahi fungsi park & ride yang berorientasi ke pengguna stasiun kereta api Cisauk, juga mengakomodasi penghobi sepeda bagi kawasan sekitarnya.